2018
DOI: 10.3389/fnbeh.2018.00179
|View full text |Cite
|
Sign up to set email alerts
|

Moral Violations and the Experience of Disgust and Anger

Abstract: Disgust is a natural defensive emotion that has evolved to protect against potential sources of contamination and has been recently linked to moral judgements in many studies. However, that people often report feelings of disgust when thinking about feces or moral transgressions alike does not necessarily mean that the same mechanisms mediate these reactions. The present study used functional magnetic resonance imaging (n = 22) to investigate whether core and moral disgusts entrain common neural systems. We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…However, such overlap was presumably biased by the presence of explicit elicitors in the description of violations (blood, urine, etc. ), as no evidence of shared activations was found when using experimental materials carefully controlled for this aspect (16).…”
Section: The Moral Network and Pccmentioning
confidence: 93%
See 2 more Smart Citations
“…However, such overlap was presumably biased by the presence of explicit elicitors in the description of violations (blood, urine, etc. ), as no evidence of shared activations was found when using experimental materials carefully controlled for this aspect (16).…”
Section: The Moral Network and Pccmentioning
confidence: 93%
“…In a pilot study, we asked proficient speakers in either French (20 volunteers: 12 females; aged 19 to 50, mean = 28.8, SD = 6.82 years) or English (37 volunteers: 19 females; aged 20 to 43, mean = 28.81, SD = 4.89) to evaluate each of the 44 dilemmas (in their corresponding language) according to the following dimensions: (i) “How much is the course of action described in the story appropriate for you?” (marked on a VAS ranging from “extremely inappropriate” to “extremely appropriate”); (ii) “How emotionally engaged were you when reading the vignette?” (marked on a VAS ranging from “not engaged at all” to “extremely engaged”); (iii) “How comprehensible was the vignette?” (marked using a scale ranging from “extremely incomprehensible” to “extremely comprehensible”). The data from these rating tasks were used to select 32 dilemmas that displayed, in both their English and French formulation, the following properties: (i) half of the dilemmas ( 16 ) were expected to describe strong violations of moral norms and thus had to be associated with the lowest appropriateness ratings and with the highest emotional engagement ratings; (ii) the remaining dilemmas were expected to describe ordinary (nonmorally challenging) behavior and were associated with the highest appropriateness ratings and the lowest emotional engagement ratings; and (iii) all dilemmas were associated with high comprehensibility ratings. Full information about the selected dilemmas and the pilot data are available in the Supplementary Materials (fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 A functional imaging study reported that insular cortex is activated as a response to disgust in both healthy participants and OCD patients. 10,11 Considering that disgust is a factor that makes treatment difficult, it can be thought that metabolic disorder of the insular cortex may be important role at response to group therapy in vaginismus patients.…”
Section: Introductionmentioning
confidence: 99%
“…We were especially interested in the role of the insular cortex since this region has been identified as relevant for disgust processing (next to a variety of other functions) in patients as well as in healthy participants. Group differences were found in both functional imaging and lesion studies (e.g., Wright et al, 2004; Knowles et al, 2018), especially when highly disgusting stimuli were used (Oaten et al, 2018).…”
Section: Introductionmentioning
confidence: 99%